UJI EFEKTIVITAS BIOLARVASIDA EKSTRAK DAUN KERSEN (MUNTINGIA CALABURA) TERHADAP LARVA AEDES AEGYPTI - Apriani, Putri Ika Nur; Ratnaningrum, Kanti; Dyah Kurnati, Ika (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2025)
Background: Aedes aegypti has a major role in the transmission of Dengue Hemorrhagic Fever (DHF). Dengue fever is caused by the dengue virus, an arbovirus in the Flaviviridae family. During the last few decades, the prevalence of dengue virus has increased dramatically throughout the world. In 2020 92.8% of all regencies/cities in Indonesia are infected with DHF. The use of plant-derived products, such as plant extracts, can be an alternative to natural larvicides. Kersen leaves contain flavonoids, tannins, saponins and alkoloids. This study aims to determine the effectiveness of biolarvaida kersen leaf extract (Muntingia calabura) against Aedes aegypti larvae. Method: This research was conducted at the Center for Research and Development of Vectors and Disease Reservoirs (B2P2VRP) Salatiga, with an experimental method using a Post Test Only Control Group Design with 10 treatment groups and 3 repetitions consisting of kersen leaf extract (Muntingia calabura) concentration of 250 ppm, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm and 6000 ppm, positive control and negative control. The results of larval mortality were analyzed using the Kruskall-Wallis test and probit analysis. Result: The test results showed that the mortality rate of the larvae was 20%, 35%, 50%, 60%, 70%, 78.33%, 85%, 96.67% for concentrations of 250 ppm, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm , 4000 ppm, 5000 ppm and 6000 ppm while a positive control of 100% and a negative control of 0% did not show the death of the larvae. The results of the probit analysis showed LC50 4047 ppm and LC90 7752 ppm. Conclusion: This study found that kersen leaf extract (Muntingia calabura) could cause death of Aedes aegypti IV instar larvae <50% at 24 hours after treatment and >50% at 48 hours after treatment.